Investigation into the rate of changes in Keplerian orbital elements for GPS satellites under solar storming - Zubinaitė, Vilma; Preiss, George (Geodesy and Cartography, 2012)
Positioning using a satellite requires defining the instantaneous positions of navigation satellites. The established positions are predicted and transmitted to the users applying satellites, and, however become degraded with accuracy in cases solar events divert the satellites from their path. Meanwhile, getting satellite coordinates with reference to the made predictions involves computing effort. The question addressed in this paper is whether orbit disturbances can be detected by examining these predictions so that computing coordinates are avoided. The paper argues that detection is possible but requires further experiments on confirmation due to the fact there have been relatively few solar storms in recent years while collecting data on satellite tracking. also, the paper also suggests that detection by examining orbital parameters is of a limited practical value when compared with the ease of interpreting satellite coordinates measured in meters. GPS palydovų orbitų Keplerio elementų kitimo dėl Saulės audrų įtakos analizė Santrauka. Padėtį nustatant globaline padėties nustatymo sistema turi būti žinomos akimirkinės dirbtinių Žemės palydovų padėtys orbitoje, tačiau dėl Saulės reiškinių įtakos dirbtiniai Žemės palydovai nukrypsta nuo jų judėjimo kelio. Išanalizavus teigiama, kad tiriant pasirinktuoju metodu galima nustatyti dirbtinių Žemės palydovų nukrypimus nuo įprastinės orbitos bei numatyti prognozes. Šiems teiginiams patvirtinti būtini tolesni eksperimentai. Reikšminiai žodžiai: GPS palydovas, Keplerio orbita, navigacinis pranešimas, Saulės aktyvumas, Saulės audra, erdvės oro sąlygos. Анализ изменений элементов Кеплера спутниковых орбит в случае солнечных бурь Резюме. Для того, чтобы было известно мгновенное положение искусственных спутников Земли на орбите, требуется определение позиции с помощью системы глобального позиционирования. Однако точность позиций спутников на орбите уменьшается из-за событий на Солнце, вследствие чего искусственные спутники Земли отклоняются от пути их движения. В статье рассматривается вопрос, можно ли обнаружить погрешности на орбите искусственных спутников Земли и предвидеть прогнозы на основании выбранного метода. Утверждается, что изменения обнаружить можно, однако для подтверждения этого требуются дальнейшие эксперименты. Ключевые слова: искусственный спутник, орбита Кеплера, навигационное сообщение, активность Солнца, солнечная буря, условия воздушного пространства.